1996
DOI: 10.1016/s0022-5223(96)70250-7
|View full text |Cite
|
Sign up to set email alerts
|

Donor-specific cellular immune response against human cardiac valve allografts

Abstract: We studied the presence of donor-specific T lymphocytes in explanted human cardiac valve allografts in vivo. From five of seven explants we propagated lymphocyte cultures in an interleukin-2 conditioned medium. Phenotyping revealed the presence of T-cell receptors in more than 95% of the lymphocytes obtained in each culture. Donor-specific cytotoxicity was demonstrated in three patients with known HLA status of the donor. Cytotoxicity was directed against only HLA class I in one patient, and against class I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…In addition to the humoral response, Hoekstra and associates have demonstrated a cellmediated immune reaction to cryopreserved homografts. T cells have been directly implicated in the inflammatory process that is associated with early and late allograft valve failure [6,7]. An important advantage of Contegra is storage in dilute, buffered glutaraldehyde, which retains leaflet-and conduit-wall compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the humoral response, Hoekstra and associates have demonstrated a cellmediated immune reaction to cryopreserved homografts. T cells have been directly implicated in the inflammatory process that is associated with early and late allograft valve failure [6,7]. An important advantage of Contegra is storage in dilute, buffered glutaraldehyde, which retains leaflet-and conduit-wall compliance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with previous reports of donor-specific immune responses generated after allograft implantation in animal models and in humans. 13,14,20,21 Taken together, there appears to be 2 important processes that may predispose cryopreserved valve grafts to structural failure. First, there is an early infiltration with myeloid cells regardless of allostimulation.…”
Section: Valve Grafts 7 Days After Implantationmentioning
confidence: 99%
“…Others reported identical in®ltration of in¯ammatory cells in cryopreserved pulmonary valve allograft explants, while the aortic valve explants were free from any cellular component [3]. Finally, Hoekstra et al demonstrated donor-speci®c cytotoxicity of in®ltrating lymphocytes found in explanted AVC [21]. Also, reviewing these studies, severe structural failure associated with in®ltration of immune competent cells is more frequently seen in pediatric patients, in whom pulmonary AVC s are predominantly implanted right-sided.…”
Section: Discussionmentioning
confidence: 98%